Circumcision revision in male children - Mohammed A. Al-Ghazo; Kamal E. Banihani (International Brazilian Journal of Urology, 2006)
OBJECTIVE: To determine indications for circumcision revision and to identify the specialty of the person who performed unsatisfactory primary circumcision. MATERIALS AND METHODS: The authors reviewed medical records of 52 cases that underwent circumcision revision over a 6-year period (1998 to 2004). Sleeve surgical technique was used for revision in patients with redundant foreskin or concealed penis, penoplasty for partial or complete degloving of the penis and meatotomy for external meatal stenosis. The mean age of children was 32 months (range 6 months to 9 years). RESULTS: Most of unsatisfactory primary circumcisions (86.7%) were performed by laymen. All patients who underwent circumcision revision had good to excellent cosmetic results. CONCLUSION: Primary circumcision performed by laymen carry a high complication rate and serious complications may occur. A period of training and direct supervision by physicians is required before allowing laymen to perform circumcision independently.